2018
DOI: 10.1016/j.tranon.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of long non-coding RNAs and MEF2C-AS1 identified as a novel biomarker in diffuse gastric cancer

Abstract: Previous studies proved that long noncoding RNAs (lncRNAs) play important role in human cancer. However, the knowledge of genome scale expression of lncRNAs and their potential biological function in gastric cancer is still lacking. Next generation RNA sequencing (RNA-seq) was performed on tumor tissues and matched adjacent normal tissues of six diffuse gastric cancer (DGC) patients. Then we performed a comprehensive analysis on lncRNAs and mRNA. Fifty-eight lncRNAs were upregulated and 54 lncRNAs were downreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 26 publications
2
23
0
2
Order By: Relevance
“…associated with this cancer histotype [76,78,79]. Namely, KMT2C loss was shown to promote EMT and was associated with poor overall survival.…”
Section: Accepted Articlementioning
confidence: 97%
“…associated with this cancer histotype [76,78,79]. Namely, KMT2C loss was shown to promote EMT and was associated with poor overall survival.…”
Section: Accepted Articlementioning
confidence: 97%
“…Long noncoding RNAs (lncRNAs), which range from 200 nucleotides to multiple kilobases and lack of protein-coding capacity, are shown to play important roles in diverse physiological and pathological processes, such as development, immune response, metabolism, self-renewal, chemoresistance, and tumorigenesis 36. Recently, the regulatory roles of FOXF1 adjacent noncoding developmental regulatory RNA (FENDRR) in human breast cancer, prostate cancer, lung cancer, and gastric cancer are demonstrated 79. However, the functions and molecular mechanism of FENDRR in colon cancer have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Expression and survival analysis were performed and it was found that the lncRNA FENDRR was significantly decreased in tumor tissue ( Figure 1B ), and patients with low FENDRR had a much shorter survival time than those with high expression ( Figure 1C ). It has been reported that FENDRR is greatly down-regulated in various cancer tissues, which induces the malignant progression and leads to poor prognosis of cancer 20 , 21 . Hence, FENDRR was selected as our research object.…”
Section: Resultsmentioning
confidence: 99%